The Implementation of Enterprise Resource Planning System within Jordanian Industrial Sector - Nassar, Mahmoud; Warrad, Lina; Siam, Yousef Abu (International Review of Management and Marketing, 2017)
This study aims to contribute to a better understanding of the implementation of enterprise resource planning (ERP) system as management accounting innovations (MAIs) in Jordan. Using in-depth interviews this paper emphasizes the main factors that influenced the process of ERP implementation were introduced and the related obstacles associated with the implementation of ERP were also highlighted. The interviewees in the Tobacco and Cigarette Company approved that both top management support is the most crucial factor to influence ERP implementation. Moreover, the interviewees claimed that training and education were the most important factor to simplify their decision to implement ERP. During the process of implementing ERP, the company could be faced with difficulties related to the implementation in practice. Thus, barriers to change could make the change process slower, hinder it, and even prevent change. The high cost of ERP implementation, high cost of consultants, and are indicated by the majority of interviewees as the most common barriers encountered during the implementation of MAIs systems. Keywords: Enterprise Resource Planning System, Management Accounting, Industrial Sector JEL Classifications: M41, O15